2020
DOI: 10.1097/fbp.0000000000000497
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperbaric oxygen on chemotherapy-induced neuropathy in male and female rats

Abstract: Chemotherapeutic agents can cause peripheral neuropathy, a deleterious side effect of cancer treatment. Hyperbaric oxygen (HBO2) treatment has shown great potential for decreasing pain in numerous clinical pain conditions and in preclinical studies. This study was designed to test whether HBO2 might also be useful for treating chemotherapy-induced peripheral neuropathy. Male and female Sprague–Dawley rats were injected with 1 mg/kg paclitaxel or vehicle every other day for 7 days to induce allodynia, followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Recent research brought strong evidence about sex differences in the development of neuropathic pain (Mogil, 2012). In our experiments, PAC produced similar PIPN in both sexes, which is in agreement with previous reports (Hwang et al, 2012;Brewer et al, 2020). We showed that DUV (10 mg/kg) pretreatment significantly reduced the development of mechanical hyperalgesia in male and female adult rats.…”
Section: Discussionsupporting
confidence: 93%
“…Recent research brought strong evidence about sex differences in the development of neuropathic pain (Mogil, 2012). In our experiments, PAC produced similar PIPN in both sexes, which is in agreement with previous reports (Hwang et al, 2012;Brewer et al, 2020). We showed that DUV (10 mg/kg) pretreatment significantly reduced the development of mechanical hyperalgesia in male and female adult rats.…”
Section: Discussionsupporting
confidence: 93%
“…And studies have already approved that there are no significant difference in oxaliplatin-induced CINP between male and female rodents. 34,35…”
mentioning
confidence: 99%
“…Finally, the combined use of HBOT plus chemotherapy have reported certain benefits. In this line, a recent study conducted by Brewer et al [ 179 ] demonstrated the effectiveness of using HBOT to prevent chemotherapy-induced neuropathy In vivo. This fact appears to be due to the various implications of HBOT in the neuronal activity and signaling [ 180 , 181 , 182 ] Kawasoe et al also observed [ 183 ] that an integrative strategy of carboplatin plus HBOT significantly reduced mortality in C3H mice with inoculated osteosarcoma cells Similar results were obtained with HBOT and chemotherapy in lung cancer cultures and animal models [ 184 ].…”
Section: Translational and Potential Applications Of Hbotmentioning
confidence: 99%